Language and style: in honour of Mick Short - McIntyre, Dan 1975-; Busse, Beatrix (Palgrave Macmillan, 2010)
"Inspired by exploring the language of poems, plays and prose, Mick Short's classic introduction to stylistics, language and style represents the state-of-the-art in literary stylistics and encompasses the full breadth of current research in the discipline. Written by leading scholars in the field, chapters cover a variety of methodological and analytical approaches, from traditional qualitative analysis to more recent developments in cognitive and corpus stylistics. Addressing the three, key literary genres of poetry, drama and narrative, Language and style is divided into carefully balanced sections. Based on original research, each chapter demonstrates a particular analytic technique and explains how this might be applied to a text from one of the literary genres. Framed by helpful introductory material covering the foundational principles of stylistics, the chapters act as practical exemplars of how to carry out stylistic analysis. Comprehensive and engaging, this invaluable resource is essential reading for anyone interested in stylistics"--